2016
DOI: 10.2174/1389557516666160630120725
|View full text |Cite
|
Sign up to set email alerts
|

New Progress in Azole Compounds as Antimicrobial Agents

Abstract: The increasing incidence of microbial resistance and newly emerging pathogens have become a serious challenge for public health. More and more efforts have been directed to the development of new antimicrobial agents with distinct mechanisms from the well-known classes of clinical drugs. The extensive clinical utilization of azole-based medicinal drugs has evoked numerous attentions, and their researches and developments have been a quite rapid developing and active highlight topic with an infinite space. Cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(37 citation statements)
references
References 0 publications
0
37
0
Order By: Relevance
“…Structural changes and the basic interactions identified from the 1,3,4‐oxadiazole scaffold, such as Sulfisoxazole (antibacterial), Oxacillin (antibiotic), Linezolid (antibacterial), Toloxatone (antidepressant), Furazolidone (antibacterial), Raltegravir (anti‐HIV) as shown in Figure . Oxadiazole compounds as the bioisostere of benzimidazoles and thiazoles, imidazoles, tetrazoles, and triazoles have attracted increasing attention. Recently, numerous researches have been devoting to oxadiazole compounds as a medicinal agent with an intent to discover novel chemical scaffold compounds with low toxicity, high bioactive and excellent pharmacokinetic property .…”
Section: Introductionmentioning
confidence: 99%
“…Structural changes and the basic interactions identified from the 1,3,4‐oxadiazole scaffold, such as Sulfisoxazole (antibacterial), Oxacillin (antibiotic), Linezolid (antibacterial), Toloxatone (antidepressant), Furazolidone (antibacterial), Raltegravir (anti‐HIV) as shown in Figure . Oxadiazole compounds as the bioisostere of benzimidazoles and thiazoles, imidazoles, tetrazoles, and triazoles have attracted increasing attention. Recently, numerous researches have been devoting to oxadiazole compounds as a medicinal agent with an intent to discover novel chemical scaffold compounds with low toxicity, high bioactive and excellent pharmacokinetic property .…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23] Pharmaceutical chemistry has produced many drugs containing a tetrazole ring as a structural element (in order to treat, AIDS, cancer and tuberculosis for example). [24][25][26][27][28] One key study by Kanakaraju and Suresh demonstrated an in vitro antimicrobial and cytotoxic evaluation of tetrazole derivatives. The results showed that the maximum antimicrobial activity was observed with seleniumcontaining tetrazole derivatives, whereas sulphur-containing tetrazole derivatives exhibited appreciable cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, we decided to introduce at this position a 1,2,3‐triazole core, a well‐known pharmacophore . Indeed, recent studies have revealed that triazole containing nucleosides exert a broad spectrum of pharmacological activities including antiviral, antimicrobial, antiproliferative, and antitumor properties …”
Section: Introductionmentioning
confidence: 99%